Androgen-induced AR-BRD4 transcriptional regulatory complex promotes malignant proliferation of osteosarcoma cells - Jia-Ming Tian; Yi-He Dong; Zi Li; Yong Zhou; Jun Huang (Cell Death Discovery)
Abstract Osteosarcoma (OS) is deemed as hormone-dependent neoplasm. Here we explored its latent mechanisms governing the interactions between specific molecules and hormones involved in OS progression. Through multiplex IHC analysis in TMA, bioinformatics analysis, and a series of in vitro and in vivo molecular assays, we identified BRD4 and sex steroid receptors were positively expressed in clinical OS tissues, simultaneously BRD4 and AR expression were elevated in the osteoblastic subtype, while ERβ predominated in the fibroblastic subtype. GEO database revealed a positive correlation between BRD4 and AR expression, while no correlation was found with ERβ expression. In vitro studies demonstrated that DHT stimulation resulted in a significant upregulation of AR and BRD4 protein expression, subsequently promoting the proliferation of OS cells. ChIP-sequencing and dual-luciferase reporter assays revealed that DHT treatment increased the distribution of BRD4 on chromatin and its overlap with AR, facilitating the formation of the AR-BRD4 transcriptional regulatory complex, which significantly increased transcription levels of AR target genes, such as PLCB4. Moreover, experiments conducted in nude mice indicated that BRD4 inhibitor, (+)-JQ1 decreased the expression of AR-related genes and inhibited OS cell growth in vivo. In conclusion, elevated expression of BRD4 in OS cells induced by androgens participates in AR-related transcriptional regulatory processes, facilitating the malignant progression of OS.